Penanaman Nilai-Nilai Karakter Islami Melalui Program Bina Pribadi Islam - Nor Habibah; Faelasuf (CV Insan Kreasi Media, 2024)
The purpose of this study is to determine the quality of Islamic character through the BPI (Islamic Personal Development) program at SDIT2 Daarussalam. The BPI (Islamic Personal Development) program at SDIT2 Daarussalam aims to instill the quality of Islamic character. This research uses qualitative descriptive analysis techniques known as field research, data collection techniques through observation, interviews and documentation. The findings of this research show that: The purpose of the implementation of the BPI (Islamic Personal Development) Program at SDIT2 Daarussalam is to instill Islamic character values and Islamic habits among students. Students should be consistently inculcated with strong ethical principles that are aligned with Islamic teachings, ensuring they are ready to contribute to society as a highly capable, independent, and pious generation. Intellectually intelligent, independent, and devout to religious or spiritual beliefs. The BPI program is implemented once a week on Friday during school hours. The implementation uses exemplary coaching techniques, coaching with habituation, and coaching with guidance, all of which are contained in the program. The results of the cultivation of these character values are seen in the polite attitude of children, always covering the aurat and getting used to practicing nahi and munkar actions. Keyword : Value planting, Islamic character, BPI (Muslim Personal Development)